PERANCANGAN TATA KELOLA MANAJEMEN DAN LAYANAN PERPUSTAKAAN BERDASARKAN METODE KUALITATIF - Al-parisy, Muhammad Iqbal; Bunyamin, Mahmudin; Hawari, Nadirsyah (UIN Raden Intan Lampung, 2020)
In this study, the authors used a qualitative method in which there were no calculations that required going directly to the location, simply by looking for references and several journals that were used as a basis. Then this method is motivated by library management governance, developing book collections, supporting and inhibiting factors, and increasing reading interest. Then also in terms of human resources, if not managed properly, these natural resources will decline compared to other resources. So both librarians and visitors and human resources (HR) must support each other in improving library management. That is why the quality level of human consciousness is important because school libraries and university libraries are an integral part of supporting the educational process. With the synergy of intellectual quality and rationality, there is no degradation of education, elements that must be fulfilled such as service, quality, abilities, and good attitudes from librarians and visitors, and the existence of library management functions with the fulfillment of Human Resources (HR) and collections that meet library standards based on Law No. 43 of 2007.